Estudo do crescimento e automontagem de nanocristais coloidais - Dalmaschio, Cleocir José (2012)
In the last two decades a remarkable progress in nanomaterials knowledge has been done, mainly in the chemical synthesis of inorganic nanocrystals via colloidal processes. Several of these advances addressed the growth control of their organization structures and morphologies. Considering this perspective, this thesis presents the results of the crystal growth of gadolinium cerium oxide (CGO), as discussed in the first chapter of the results. In this system, the colloidal state effect on the growth mechanism by oriented attachment (OA) was evaluated. In the process of OA basically two approaches can be considered for growth. An associated effect of the collision of the particles mutually oriented that takes place in the dispersed colloidal state and other through attachment induced by rotation and alignment that was used for the growth of CGO, controlling the pH of the system. In this process CGO nanorods were attained during the hydrothermal processing of the colloidal suspension. In the second chapter of results, the crystal growth using an organic solvent was analyzed, in which a weakly flocculated colloidal state was achieved and led to the growth of TiO2 nanorods. The stability of nanorods was evaluated at different times of solvothermal treatment allowing the evaluation of the thermodynamic evolution of the structure. In this process, nanorods structures were divided into smaller structures by a detachment mechanism. By using the high resolution transmission electron microscopy technique the different stages of the process were evaluated, initially identifying formation mechanism by OA to growth the nanorods. Afterwards, a surface diffusion drives to a thermodynamically stable structure, followed by a detachment mechanism that leads to bipyramidal structures. Considering the two systems evaluated, it was concluded that by mastering the interparticle interactions it was possible to growth anisotropic structures, but their stability is constrained by the principles of thermodynamics. In order to control the self-assembly of nanocrystals, the third chapter of results presents the superlattices structures built with zirconium oxide colloidal nanocrystals. In this system, by using nanoparticles with a narrow size distribution and by controlling the interaction between the solvent and the organic molecule bound to the nanocrystals surface, self-assembled superlattices were attained. By controlling these interactions, compact structures were obtained resulting in single and multilayer. The results pointed out that the ability to organize nanocrystals into hierarchical structures, depends crucially on the ability to understand and control of the interparticle interactions.